PROTOTYPE METHOD PADA APLIKASI SCHEDULER BERBASIS MOBILE - Nurmalasari, Nurmalasari; Adinda, Nabila; Masturoh, Siti (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
PT United Tractors is currently implementing digitalization in its various activities. In its implementation, delivering information and archiving documents in the PSD4 Service Division still have obstacles due to the lack of effective and efficient access to information needed to do work. To overcome these problems, the solution that can be provided is to develop a mobile-based document filing system using the Flutter framework to maximize the development of mobile-based systems. For developers to interact directly with teams related to application capabilities, this system development method uses the Prototype method, which has 5 phases: Communication, Quick Plan, Modelling Quick Design, Construction of Prototype, and Development, Delivery, and feedback phases. The result of this research is an Android-based Scheduler Mobile document archiving application that has been made based on the steps in the prototype method. Testing using Black Box and Flutter DevTools is done to find out the results of the application that has been made. Black Box and Flutter DevTools testing results show that the application can run as expected.